Challenges facing essential workers: a cross-sectional survey of the subjective mental health and well-being of New Zealand healthcare and 'other' essential workers during the COVID-19 lockdown. Issue 7 (19th July 2021) - Bell, Caroline; Williman, Jonathan; Beaglehole, Ben; Stanley, James; Jenkins, Matthew; Gendall, Philip; Rapsey, Charlene; Every-Palmer, Susanna
Abstract : Objectives: To compare psychological outcomes, experiences and sources of stress over the COVID-19 lockdown in New Zealand in essential workers (healthcare and 'other' essential workers) with that of workers in nonessential work roles. Design: Online cross-sectional survey. Setting: Conducted in New Zealand over level 4 lockdown in April/May 2020. Participants: Findings from employed participants (2495) are included in this report; 381 healthcare workers, 649 'other' essential workers and 1465 nonessential workers. Primary and secondary outcome measures: Measures included psychological distress (Kessler Psychological Distress Scale (K10)), anxiety (Generalised Anxiety Disorder (GAD-7)), well-being (WHO-5), alcohol use, subjective experiences and sources of stress. Differences between work categories were quantified as risk ratios or χ 2 tests. Results: After controlling for confounders that differed between groups of essential and nonessential workers, those in healthcare and those in 'other' essential work were at 71% (95% CI 1.29 to 2.27) and 59% (95% CI 1.25 to 2.02) greater risk respectively, of moderate levels of anxiety (GAD-7 ≥10), than those in nonessential work. Those in healthcare were at 19% (95% CI 1.02 to 1.39) greater risk of poor well-being (WHO-5 <13). There was no evidence of differences across work roles in risk for psychological distress (K10 ≥12) or increased alcohol use. Healthcare and 'other' essential workers reported increased workload (p<0.001) and less uncertainty about finances and employment than those in nonessential work (p<0.001). Healthcare and nonessential workers reported decreased social contact. No difference by work category in health concerns was reported; 15% had concerns about participants' own health and 33% about other people's health. Conclusions: During the pandemic lockdown, essential workers (those in healthcare and those providing 'other' essential work) were at increased risk of anxiety compared with those in nonessential work, with those in healthcare also being at increased risk of poor well-being. This highlights the need to recognise the challenges this vital workforce face in pandemics.